Study of energetic properties of different tree organs in six Olea europaea L. cultivars - G. Sala (Nature Portfolio, 2021)
Abstract Pruning is an important horticultural practice for the management of olive orchards (Olea europaea L.) that generates a considerable amount of residues every year. Olive orchards are increasingly expanding beyond the Mediterranean Basin to new growing Countries (Australia, California, Argentina, Chile and Uruguay) and this will certainly lead to larger availability of pruning material. Currently, the interest in use of olive tree pruning residues for energy purposes is increasing but unfortunately, the information on the differences among organs of the tree, in terms of calorific value and ash content, is scarce. Another unknown aspect is the effect of cultivar vigour on dry matter partition among different tree organs, these are important traits to establish the energetic quality of pruning residues. The aim of this research was to study energetic aspects of six olive cultivars, largely grown in the Sicilian olive industry and characterized by different vigour. The trees taken into consideration in the study were selected in an experimental orchard to avoid any effect due to differences in environmental conditions and management. The energetic characteristics, calorific value and ash content, were evaluated for the various tree organs particularly shoots, leaves and branches; also root system was evaluated, although the roots can only be used once the trees are uprooted. Significant differences were observed in the calorific values among the different tree organs and the cultivars. Regarding the ash, shoots and leaves showed the highest content with respect to the other organs, thus causing a possible tendency in slagging with fouling and corrosion of boiler components.